Análisis de la satisfacción del consumidor final en relación a la tarifa del agua potable del cantón Lomas de Sargentillo, provincia del Guayas Ecuador - De La Torre Aspiazu, Wilson William (2022)
The issue related to the analysis of the satisfaction of the final consumer in relation to the rate of drinking water in the canton Marcelino Maridueña is due to the different situations and conflicts that arise due to the supply of water and the limited satisfaction of the consumer; high costs, limited consumption and lack of expansion of the water system are also involved; The general objective is to analyze the factors that influence the dissatisfaction of the population, in addition to investigating the perception of the inhabitants regarding the treatment, distribution, tariff and quality of drinking water. The methodology used is a descriptive research that uses a qualitative and quantitative approach; where the population is all those inhabitants who are made up of families and who are part of the consumption and supply of water. The results obtained from 66 families surveyed reflect that the quality, inconveniences, controls, among other relevant factors in user satisfaction are very limited. The proposed proposal is related to the guidelines for improvements and quality evaluation; In conclusion, new strategies and guidelines are required for water treatment, both in the distribution and management of the pollutants it generates, where the applied policies would allow a better standard of living for citizens and the regulation and compliance of the measures. applied.